2012
DOI: 10.1021/ci300141k
|View full text |Cite
|
Sign up to set email alerts
|

The Large Scale Conformational Change of the Human DPP III–Substrate Prefers the “Closed” Form

Abstract: Human dipeptidyl peptidase III (DPP III) is a two domain metallo-peptidase from the M49 family. The wide interdomain cleft and broad substrate specificity suggest that this enzyme could experience significant conformational change. Long (>100 ns) molecular dynamics (MD) simulations of DPP III revealed large range conformational changes of the protein, suggesting the pre-existing equilibrium model for a substrate binding. The binding free energy calculations revealed tighter binding of the preferred synthetic s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
59
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 25 publications
(66 citation statements)
references
References 42 publications
5
59
0
Order By: Relevance
“…In this position, the inhibitor interacts by means of electrostatic and van der Waals forces with the residues of the "lower" domain (residues Ser108, Phe109, Asp111, Leu161, Tyr318, Glu327) and the "upper" domain (residues Phe556 and Arg669). However, whereas during the simulation of ligand-free protein 35 the domains progressively approached each other and the Rg decreased (the initial value was about 28.5 Å and the final one about 26.5 As a result of the domains motion, several hydrogen bonds were formed between the inhibitor and the residue Ser108, Glu316, Ile386, Ala416, and His565 (Fig. 6).…”
Section: Results Of the Molecular Dynamics Simulation Of The Dpp III mentioning
confidence: 99%
“…In this position, the inhibitor interacts by means of electrostatic and van der Waals forces with the residues of the "lower" domain (residues Ser108, Phe109, Asp111, Leu161, Tyr318, Glu327) and the "upper" domain (residues Phe556 and Arg669). However, whereas during the simulation of ligand-free protein 35 the domains progressively approached each other and the Rg decreased (the initial value was about 28.5 Å and the final one about 26.5 As a result of the domains motion, several hydrogen bonds were formed between the inhibitor and the residue Ser108, Glu316, Ile386, Ala416, and His565 (Fig. 6).…”
Section: Results Of the Molecular Dynamics Simulation Of The Dpp III mentioning
confidence: 99%
“…The ETGE motif of DPP III resides in a loop, on the surface of the catalytic domain (see Figure 1), and we found that it is the most flexible part of the human DPP III. [12] Besides in human, this loop was identified in DPP IIIs found in animals and fungi, as well. However, DPP IIIs from plant and bacteria lack this loop (see Supplemental materials).…”
Section: Introductionmentioning
confidence: 94%
“…[12] The zinc ion was described with noncovalent parameters only (charge +2.0 e, and parameters for van der Waals interactions: raduis 1.22 Å, and energy minima of 0.250 kcal mol -1 ).…”
Section: All-atom MD Simulationsmentioning
confidence: 99%
See 2 more Smart Citations